Sealing ability of three different materials to repair furcation perforations using computerized fluid filtration method - Cemre Koç; Berna Aslan; Zuhal Ulusoy; Hasan Oruçoğlu (Tabriz University of Medical Sciences, 2021)
Background. The present study aimed to evaluate the sealing ability of three different calcium silicate-based materials in furcation perforations. Methods. Seventy-six human mandibular molar teeth were selected. Perforations were created in the center of the pulp chamber floor. The experimental teeth were randomly divided into three groups (n=22). Perforations were repaired with MTA Angelus, Endocem MTA, or EndoSequence BioCeramic Root Repair Material Fast Set Putty (BC-RRM Putty). Microleakage of the different repair materials to be tested was measured by computerized fluid filtration method at 24- and 72-hour intervals. Results. For each time interval, no statistically significant difference was observed between the groups. For Endocem MTA and BC-RRM Putty groups, the difference between the leakage values measured at both periods was not statistically significant (P>0.05). However, there was a significant difference for the MTA Angelus group (P<0.05). Conclusion. All the calcium silicate-based materials used in the present study showed similar performance in repairing furcation perforations at 24- and 72-hour intervals.